Unveiling the Impact of Sustainable Interior Design Criteria on Hotel’s Operational Performance Effectiveness and User’s Hedonic Consumption - Che Abdullah, Siti Noorfairus; Khalil, Natasha; Haron, Siti Norsazlina; Hamid, Md Yusof; Yan, Yan (International Journal of Sustainable Construction Engineering and Technology, 2023)
Performance effectiveness in the hotel’s operational stage is significant for hotel industry as the industry relies on customer satisfaction towards the service. Fulfilling the customer’s satisfaction and users’ hedonic on the aesthetic appearance, interiors, room decorations, and furnishings is crucial for hotel’s operational and facilities management concept. However, awareness the management of tangible interiors and aesthetic performance on sustainable interiors products are still lacking in the hotel’s operational performance. This study aims to close the loop between the sustainable interior design (SID) and facilities management, by identifying the criteria of SID relating to hotel’s operational performance and user’s hedonic consumption. A semi-structured interview was carried out this study involving three professionals; architect, interior designer, GBI facilitator, in various green hotels project. The data is analysed using ATLAS.ti9© qualitative software. The findings revealed that there are seven (7) sustainable ID criteria consists of biophilic, energy efficiency, water consumption, health and social flexibility, environmental comfort, ergonomics, and green awareness. This study is significant for the hoteliers in identifying critical elements contributed to the successful performance in hotel’s operational stage using sustainable interiors.